Ramifications of coronary angiography with effect to time comparing two groups: undergoing off pump coronary artery bypass grafting within or more than seven days of coronary angiography - Loona, Manpal; Mahant, T. S. (International Surgery Journal, 2020)
Background: Acute kidney injury (AKI) following off pump coronary artery bypass grafting (OPCABG) within short interval from coronary angiography (CAG) has been well documented. This prospective study is aimed to delineate perioperative effects and effects of elective 7 days interval between CAG and off pump CABG, to observe its outcome on renal functions. Methods: The present study was conducted in a total of 1102 consecutive patients who underwent coronary angiography following coronary artery bypass surgery in Fortis hospital, Mohali. Patients were divided into 2 groups - group A (patients undergoing CABG within 7 days of CAG) and group B (patients undergoing CABG beyond 7 days of CAG). Comparison was made between the two groups, in relation to the timing between CAG and CABG, with its impact on perioperative renal functions. Results: Statistically it was found highly significant higher values of 1st and 3rd day serum creatinine and high incidence of postoperative AKI in patients of group A in comparison to patients of group B. Conclusions: Thus, our study confirms that patients with a shorter interval between CAG and subsequent OPCAB are more likely to present higher peak creatinine level as well as lower minimum eGFR. A gap of 7 days for elective cases is more likely to present less postoperative AKI.